SWOT Analysis and QSPM Matrix in Chicken Egg Marketing in Banyuwangi: A Case study of PT Supermama Farm Banyuwangi - Imam Ramadani Nugroho; Sefri Ton; Ninik Sri Rahayu Wilujeng (International Journal of Management Science and Application, 2024)
The laying hen farming business is one of the contributors of protein food to the community but faces stiff competition in business. This research examines the external and internal factors of the laying hen cultivation business at PT. Supermama Farm. The research method is descriptive. The analysis tools are SWOT analysis and QSPM. The research results show that the total IFAS value is 3,238 and the EFAS value is 3,029. This condition is in quadrant I. The main strategy taken by the company is trying to maintain chicken performance so that the quality of the eggs is high, maintaining relationships with the social environment and customers (TAS 7.140), and guaranteeing product quality (7.082).